2008
DOI: 10.5694/j.1326-5377.2008.tb01986.x
|View full text |Cite
|
Sign up to set email alerts
|

How do Australian patients rate their general practitioner? A descriptive study using the General Practice Assessment Questionnaire

Abstract: Objective: To report patient responses to the General Practice Assessment Questionnaire (GPAQ) as a measure of satisfaction with health care received from Australian general practitioners. Design, setting and participants: A clustered cross‐sectional study involving general practice patients from 30 randomly selected general practices in Victoria. Between January and December 2005, a screening survey, including a postal version of the GPAQ, was mailed to 17 780 eligible patients. Main outcome measure: Scores o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 19 publications
3
36
0
2
Order By: Relevance
“…As reported elsewhere,16 we found that patient satisfaction increased with the amount of time spent with their GP. While relieving the time pressures that many Australian GPs experience19 may not be a viable option, the recent recommendation made by Arthritis Australia in support of specialist OA practice nurses warrants further exploration,20 as they are the health care professionals most likely to provide self-management support for patients with chronic disease 21…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As reported elsewhere,16 we found that patient satisfaction increased with the amount of time spent with their GP. While relieving the time pressures that many Australian GPs experience19 may not be a viable option, the recent recommendation made by Arthritis Australia in support of specialist OA practice nurses warrants further exploration,20 as they are the health care professionals most likely to provide self-management support for patients with chronic disease 21…”
Section: Discussionsupporting
confidence: 88%
“…Despite this, little has been known about satisfaction with GP care for OA in Australia, as most studies have focused on satisfaction with primary care in general 1618. The mostly high patient satisfaction ratings reported in our study are consistent with more general research concerning primary care.…”
Section: Discussionsupporting
confidence: 87%
“…However, our data showed 89% of patients were able to complete a comprehensive health risk survey in less than 15 minutes, and 99% were able to do so prior to their consultation [28]. Given that the majority of general practice patients wait on average 11-30 minutes before an appointment [32], the completion of electronic assessments prior to consultation is highly feasible. Our data indicate that this approach does not disrupt the clinic, increase patient waiting times, or increase staff burden [28].…”
Section: Improving the Comprehensiveness And Accuracy Of Clinical Infmentioning
confidence: 99%
“…For an individually randomised trial, a total of 50 young people were required in both study arms to detect an absolute difference of 20% in mean scores on the YFHS-WHO + questionnaire between the study arms (standard deviation = 25%, alpha = 5%, power = 80%, 2-sided test). To allow for clustering by municipality, the sample size for the individually randomised trial was inflated by a factor of 4.6 (design effect), assuming that the intra-cluster correlation (ICC) was 0.163 for 10 clusters, based on a study using a similar tool (Potiriadis et al 2008). Hence, based on the assumptions we would require 23 individuals per municipality (that is a total of 230 young people).…”
Section: Methodsmentioning
confidence: 99%